2023
DOI: 10.1007/s11064-023-03916-w
|View full text |Cite
|
Sign up to set email alerts
|

Active Clinical Trials in Hepatic Encephalopathy: Something Old, Something New and Something Borrowed

Abstract: Hepatic encephalopathy (HE) is a potentially reversible neurocognitive syndrome that occurs in patients with acute or chronic liver disease. Currently, most of the therapies for HE aim to reduce ammonia production or increase its elimination. To date, only two agents have been approved as treatments for HE: lactulose and rifaximin. Many other drugs have also been used, but data to support their use are limited, preliminary or lacking. The aim of this review is to provide an overview and discussion of the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Beyond its nutritional value, GOS is crucial in dietary supplements aimed at infants and the elderly, supporting gut health and overall wellness [53]. In medical contexts, lactulose, a derivative of GOS, is utilized to manage conditions such as hyperammonemia and portosystemic encephalopathy [54]. Importantly, GOS supplementation in infants has been linked to lower risks of allergic conditions, such as eczema, underscoring its potential in allergy prevention.…”
Section: Functional Properties Of Polymeric Oligosaccharides 21 the R...mentioning
confidence: 99%
“…Beyond its nutritional value, GOS is crucial in dietary supplements aimed at infants and the elderly, supporting gut health and overall wellness [53]. In medical contexts, lactulose, a derivative of GOS, is utilized to manage conditions such as hyperammonemia and portosystemic encephalopathy [54]. Importantly, GOS supplementation in infants has been linked to lower risks of allergic conditions, such as eczema, underscoring its potential in allergy prevention.…”
Section: Functional Properties Of Polymeric Oligosaccharides 21 the R...mentioning
confidence: 99%
“…IR procedures, such as TIPS and spontaneous portosystemic shunts (SPSS), play a pivotal role in the development of HE, particularly among patients with chronic liver disease [41]. Techniques like shunt occlusion and TIPS reduction have shown efficacy and safety in alleviating neurological symptoms in individuals with refractory HE, focusing on managing portal-systemic shunts integral to its pathophysiology [41,42]. A review of ongoing clinical trials in HE identified 17 active studies as of August 2022, with over 75% of these trials in phase II (41.2%) or phase III (34.7%) stages [1].…”
Section: Review Of Clinical Studies and Trialsmentioning
confidence: 99%
“…Hepatic encephalopathy (HE) is a syndrome of central nervous system dysfunction caused by acute and chronic liver failure or various portal systemic shunt disorders; it is based on metabolic disorder and excludes other known types of encephalopathy [ 1 ]. HE is the third most serious complication of decompensated liver cirrhosis and affects at least 30% of people with cirrhosis [ 2 ]. HE is characterized by a series of neuropsychiatric syndromes as diverse as subclinical changes and coma, including abnormal changes in cognitive function, emotion, behavior, and motor function.…”
Section: Introductionmentioning
confidence: 99%